(untitled) (REDEL. Revista Granmense de Desarrollo Local, 2021)
The application of Computer Science in different areas of knowledge constitutes an important field of professional action for specialists in the area, as the results obtained, mainly from the design and application of information management systems, contribute to the organization and processing of data quickly and safely. It is precisely in this field that the research presented was developed, based on the need to optimize actions for the control and processing of information related to the health process in the Department of Veterinary Medicine in the Delegation of Agriculture of Granma. The general objective was oriented to develop a computerized system for the management of the information regarding the epizootiological control. Theoretical (analysis-synthesis and historical-logical) and empirical (interview) methods were used to define the theoretical foundations and gather information. The proposed application is based on free technologies, multiplatform and on a layered architecture; PHP 5 is used as the programming language on the server side, JavaScript, HTML, CSS 3 on the client side and as a CodeIgniter framework, manifesting the work with the Model-View-Controller architectural pattern. MySQL is used as the database management system, as the XAMPP Control Panel web server and XP development methodology (Extreme Programmin). The application of the web-based computer system for epizootiological control generated improvements in administration and decision-making, favoring the reliability and security of the data